Mayflies and long-distance runners: The effects of new business formation on industry growth - Oliver Falck (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2005)
This paper analyzes the effects of new business formation on industry growth. Dynamic panel techniques are used to test two hypotheses. First, does hit-andrun competition secure efficiency in an industry? Second, do innovative startups lead to amplified innovations by diminishing the knowledge filter? The results illustrate how new businesses can be viewed as either mayflies or longdistance runners.
Keywords: L16; M13; O31; O41; 330; Entry and exit; growth; hit-and-run competition; innovation; dynamic panel techniques